Adolescence continuity, change, and diversity - Cobb, Nancy J.
Nancy Cobb’s Adolescence, recognized as one of the leading texts in the field, provides an up-to-date and thorough review of current research and theory. Praised for its clear and engaging writing style, this highly acclaimed text is distinguished by its excellent coverage of gender, ethnicity, and identity, and for its treatment of differences between early and late adolescence. Research Focus Boxes in each chapter provide comprehensive coverage of developmental research methods. Additionally, In More Depth boxes on topics of special interest to students extend the coverage of each chapter.